USM HOSTED HKBU DELEGATES FOR OVERSEAS FIELD STUDY TOUR - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, June 2017 – The School of Distance Education (SDE), Universiti Sains Malaysia (USM), played host to a delegation from the Hong Kong Baptist University (HKBU) who has selected Penang and Kuala Lumpur as the locations for their MSc of Applied Economics field study programme during their visit to Malaysia recently.